Development and psychometric properties of the Person-centered Palliative Care Nursing Instrument (PPCNI) in the Philippines - Gil P. Soriano; Kathyrine A. Calong Calong; Rudolf Cymorr Kirby Martinez; Hirokazu Ito; Yuko Yasuhara; Evalyn Abalos; Tetsuya Tanioka (Belitung Raya Foundation, Indonesia, 2023)
Background: Over the years, a few tools and instruments have been developed to assist in the assessment within a palliative care setting. However, many of these tools and instruments do not reflect a person-centered palliative care model. Objective: This study aims to develop a Person-centered Palliative Care Nursing Instrument (PPCNI) in the Philippines. Methods: An exhaustive search of the literature was conducted to develop a pool of items for the instrument. The validity of the instrument was evaluated using the content validity index (CVI), while the factor structure was assessed using exploratory factor analysis (EFA) using maximum likelihood estimation with Promax rotation. Also, the internal reliability was evaluated using Cronbach’s alpha. Results: EFA yielded three factors: 1) Caring as maintaining person’s dignity (13 items), 2) caring as empowerment of person’s autonomy (14 items), and 3) caring as understanding person’s momentary concerns (10 items). Whereas the internal consistency reliability of these subscales appeared excellent (i.e., 0.95, 0.96, and 0.93, respectively), the Cronbach’s alpha for the overall scale was 0.98. The item-total correlation coefficients were >0.30 for all items, ranging from 0.310 to 0.726. Conclusion: Findings support a three-factor, 37-item PPCNI that can be used in clinical practice to ensure that nurses provide palliative care based on patient needs and preferences.